Endocavitary pacemaker implanted in a 2 years old child due to epicardial system failure - Michel Cabrera Ortega; Ailema A. Alemán Fernández; Dunia B. Benítez Ramos (ECIMED, 2014)
Historically, epicardial pacing has been the preferred pacing system in children, due to anatomical difficulties of venous access and the absence of endocardial electrodes with diameters suitable for small hearts. We present a case of a 2 years old with a history of coarctation of the aorta and outflow tract obstruction of the left ventricle by fibrous rim, as a complication of the surgical correction the patient presented a complete atrioventricular blockage, requiring implantation o f epicardial permanent pacemaker. During follow ups the patient presented syncopal episodes associated with cable stimulation failure due to an increased threshold, so he required a second operation to reposition the electrode.Due to repeated failure of stimulation for the same reason, we decided to implement an endocavitary system